Deployment of an orthopaedic app in leveraging sociodigital medical education for the undergraduate - Goh, Kian Liang; Noor Rahin, Mohd Shahidan; Abdul Razak, Ardilla Hanim; Sharifudin, Mohd Ariff; Awang, Mohd Shukrimi (2016)
Product description: The role of mobile applications in medical education is growing exponentially by day. To leverage mobile technology in the medical education, we designed a hybrid mobile app designated as OrthoBoard based on the undergraduate orthopaedic curriculum, targeted to deliver the clinical and practical aspects of orthopaedic training. Methodology: The frontend of the mobile app was created using Ionic framework. The content consisted of Basic Orthopaedic Skills (BOSC), Basic Trauma and Resuscitation Skills (BTRC), Islamic Input in Orthopaedic (IIIO) and Cheatsheets. Results and Discussion: Since its inception, we received a combined downloads of more than 600 in the Google Play and Apple Appstore. with a rating of 4.9/5 on Google Play with many positive reviews. Students’ direct feedback suggested that the app was successful in creating interactive learning via mobile technology. Conclusion: This orthopaedic app is unique as it caters specifically to our orthopaedic curriculum and the students’ need for orthopaedic knowledge which is not found in other apps or e-learning modules. Through this app, we hope to make medical education engaging, fun and dynamic for the medical students.